Application development to measure PKP-PK readiness in aviation operations - Sri Mulyani; Rianto Rianto (Compiler, 2022)
PKP-PK (Pertolongan Kecelakaan Penerbangan dan Pemadam Kebakaran) is the most important thing in preventing aviation accidents, with the aim of preventing or reducing losses to fatalities. Based on General Air Transportation Regulation KP Number 14 of 2015, every airport is required to provide and provide PKP-PK services in accordance with the required airport PKP-PK categories. Thus the feasibility of airport operations is an important factor in an airport, measuring readiness for airport operational feasibility is important in order to meet general air transportation regulations KP No. 14 of 2015. With an application that can be used to measure airport operational readiness, it is increasingly providing convenience to airport managers for airport operational readiness.